Dental radiographic information of term newborn babies within the first month: Analyzing five radiographic cases along with physical attributes in Japan. (February 2023) - Oka, Hiroko; Asao, Yuria; Nakao, Naoki; Mitsuhata, Chieko; Matsumoto, Yoriaki; Nomura, Ryota; Kakimoto, Naoya; Nagao, Masataka; Kozai, Katsuyuki
Highlights: Little dental radiographic data are available for tooth development in newborns. We studied the radiological and autopsy findings of five term babies. Deciduous teeth were calcified at birth (day 0 of life) The first permanent molar was calcified at 1 month. The mandibular symphysis was incompletely ossified in the first month. Abstract: Background: Although dental radiography is a valuable tool for age estimation in forensic anthropology and odontology, very limited radiological data are available regarding tooth development in healthy newborn babies during the first month of life. Aim: This study aimed to describe the radiological findings of tooth development in babies aged 0 days to 1 month. Design: We analyzed the postmortem findings of five newborn babies with no known natural cause of death who had undergone autopsy, computed tomography (CT), and dental radiography. We estimated the gestational age for the babies aged 0 days and analyzed the condition of mandibular symphysis, existence of tooth germs, and presence or absence of calcification of the first permanent molars of all the babies. Results: The calcified form of 20 deciduous teeth, tooth germs of the permanent upper and lower first molars, and non-calcified mandibular symphysis were observed in each case. However, calcification of the first permanent molar was observed in only two 1-month-old babies. Conclusion: The dental radiographic findings and anthropometric measurements of non-skeletonized, non-mummified term babies confirmed calcification of all the deciduous teeth and the first permanent molar at the age of 0 days and 1 month, respectively.